LANGUAGE USE AT AL-AMIN CHILDREN ISLAMIC BOARDING SCHOOL IN SUKOHARJO, CENTRAL JAVA (A CASE STUDY) - Qanitah Masykuroh (Universitas Muhammadiyah Surakarta, 2005)
This paper is abstracted from the findings of a case study aimed at describing the codes used by children at Al-Amin Children Islamic Boarding School in Sukoharjo, Central Java. The majority of children at this Children Islamic Boarding School are bilinguals. They use javanese as their first language and Indonesian as their second language. However; they live in a specific language condition in which they should only use Indonesian in their daily activities. The analysis shows that the codes used by children are in the form of language (Indonesian and Javanese), speech level (ngoko, madya and krama), and style (formal, informal and brief). The differentiation of function between Indonesian and Javanese is not quite clear. Frequently, children use both Indonesian and Javanese in many occassions. As a result, there amny code switching and code mixing in their speech. Code swicthing occured in their speech to function: (1) count (2) think aloud (3) show annoyance (4) give emphasis (5) give reinforcement (6) give respect, and (7) make quotation. The result also shows that code mixing indicates that children's mastery of Indonesian and Javanese is still lacking. Besides, it also indicates that they get confused with language function.Key words: code forms, code function, code switching, and code mixing